Family-Related Factors Associated with Stunting - Sangadji, Namira Wadjir; Setyowati, Sulis; Kusumaningtiar, Devi Angeliana; Shorayasari, Susi; Rusdy, Mirta Dwi Rahma (Jurnal Kesehatan, 2025)
Stunting remains a significant nutritional concern for the Indonesian government due to its impact on human resource quality. The Puskesmas (Community Health Centre) in Duren Sawit Subdistrict has experienced an increase in the proportion of stunting cases, rising from 9.06% to 10.5% over the last three months. Objective: This study aims to identify family factors associated with stunting in children aged 12-59 months in the Puskesmas of Duren Sawit Subdistrict for 2023. This research adopts a case-control study design with 41 cases and 41 controls. Cases were identified based on a compilation of data on stunted children at the health center, while controls were children without a stunting diagnosis. Sampling was conducted using the simple random sampling method. Data collection involved direct interviews with the mothers of the children and a review of medical documents. Data analysis was performed using the Chi-square test. Family income with less than minimum wage has the highest PR value compared to other variables, namely 9.68 (95% CI 2.48- 37.78), so it can be concluded that family income with less than minimum wage is the variable that most influences stunting. The recommendation in this study is that cooperation between the Duren Sawit Subdistrict Health Center and the local government, involving community leaders and an interactive approach, is necessary to provide education on nutrition and family financial management for the effectiveness of stunting prevention.